A new method of constructing cyclic symmetric conservative chaotic systems and improved offset boosting control. (May 2022) - Zhang, Zefeng; Huang, Lilian; Liu, Jin; Guo, Qiang; Du, Xiuli
Abstract: Based on the special structure of cyclic symmetric systems and the characteristics of conservative systems, a new method for constructing cyclic symmetric conservative chaotic systems(CSCCSs) is proposed, which can be used to construct three-dimensional(3D) system and above. Taking 3D system, four-dimensional(4D) system and five-dimensional(5D) system as examples, the construction method is introduced, and the conservation and chaotic features are verified by the determination of divergence, equilibrium points, and Lyapunov exponents(LEs), which proves the feasibility of the new method. Then, we carry out the improvement of the offset boosting control for the three constructed CSCCSs. The results show that this new control method can change the average value of the corresponding state variables, offset the variables and realize the polarity conversion of the signal. Finally, the new system is implemented by using the digital signal processor(DSP) hardware platform. Highlights: A new method for constructing cyclic symmetric conservative chaotic systems is proposed. Three examples are used to prove the feasibility of the construction method. An improved offset boost control method is proposed, which can offset the variable and realize the polarity conversion of the signal.